2013
DOI: 10.1371/journal.pone.0065183
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Relationship and Structural Characterization of the EPF/EPFL Gene Family

Abstract: EPF1-EPF2 and EPFL9/Stomagen act antagonistically in regulating leaf stomatal density. The aim of this study was to elucidate the evolutionary functional divergence of EPF/EPFL family genes. Phylogenetic analyses showed that AtEPFL9/Stomagen-like genes are conserved only in vascular plants and are closely related to AtEPF1/EPF2-like genes. Modeling showed that EPF/EPFL peptides share a common 3D structure that is constituted of a scaffold and loop. Molecular dynamics simulation suggested that AtEPF1/EPF2-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 33 publications
2
49
0
Order By: Relevance
“…Similar to the Arabidopsis EPF/EPFL peptides, the GAD1 prepropeptide contained an N-terminal secretory signal peptide and a mature peptide with a conserved region of six cysteine residues (Supplemental Figures 10 and 11 and Supplemental Table 1). The six conserved cysteine residues are essential for proper formation of intramolecular disulfide bonds that are critical for peptide function (Abrash and Bergmann, 2010;Jewaria et al, 2013;Katsir et al, 2011;Lee et al, 2012;Ohki et al, 2011;Takata et al, 2013). (A) The target gene was mapped between the markers M10 and RM5485 on the long arm of chromosome 8.…”
Section: Gad1 Encodes a Predicted Small Secreted Cysteine-rich Peptidmentioning
confidence: 99%
“…Similar to the Arabidopsis EPF/EPFL peptides, the GAD1 prepropeptide contained an N-terminal secretory signal peptide and a mature peptide with a conserved region of six cysteine residues (Supplemental Figures 10 and 11 and Supplemental Table 1). The six conserved cysteine residues are essential for proper formation of intramolecular disulfide bonds that are critical for peptide function (Abrash and Bergmann, 2010;Jewaria et al, 2013;Katsir et al, 2011;Lee et al, 2012;Ohki et al, 2011;Takata et al, 2013). (A) The target gene was mapped between the markers M10 and RM5485 on the long arm of chromosome 8.…”
Section: Gad1 Encodes a Predicted Small Secreted Cysteine-rich Peptidmentioning
confidence: 99%
“…In Arabidopsis, the EPF family consists of two EPF peptides (EPF1 and EPF2) and nine EPF-like peptides (EPFL1 to EPFL9). EPF/EPFL genes are present in mosses, monocots, and dicots (Takata et al, 2013). Overexpression of EPF1, EPF2, EPFL4, and EPFL5 inhibits stomatal development when ectopically overexpressed (Hara et al, 2009).…”
Section: Cysteine-rich Peptidesmentioning
confidence: 99%
“…NMRderived structural information showed that STOMAGEN represents two antiparallel b-strands connected by a loop (Ohki et al, 2011) (Figure 3). Additional 3D structure modeling revealed that EPF1/EPF2-LIKE (EPFL) peptides form a disulfide bond in the loop region absent in EPFL9/STOMAGEN-LIKE peptides (Takata et al, 2013). Recent studies demonstrated direct binding of EPF peptides to ERECTA family receptor kinases .…”
Section: Cysteine-rich Peptidesmentioning
confidence: 99%
“…AtsORF0359 had eight cysteines in the coding sequence; this even number of cysteine residues is often found in functional cysteinerich peptides such as LURE and EPF/ EPFL. 2,24 However, an odd number of cysteine residues was conserved between OsORF0359L and AtsORF0359. The start codon of OsORF0359L should be identified to predict this functional sORF accurately.…”
Section: Rice Homologs Of Arabidopsis Sorfsmentioning
confidence: 99%
“…[14][15][16] As well as sequences encoding CLE peptides, those encoding other peptide hormones (ROT4, RTFL/DVL, EPF/ EPFL) are also conserved in higher plant species. [17][18][19][20][21][22][23][24][25][26] The conservation of coding sequences among multiple plant species provides good evidence for the functionality of these peptides.…”
mentioning
confidence: 99%